Case Analysis On Violence Against Children Assessed From A Legal And Criminological Perspective - Abraham Ethan; Brandon Hartanto (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
Crimes committed against children are not new. Even with the development of technology, we can see that this often happens and is even used as a joke on social media platforms. Protection of children is firmly recognized in the Indonesian Constitution and various laws and regulations in Indonesia. Therefore, law enforcers who represent the state have an obligation to protect them if they become victims of violence and criminal acts. Apart from a legal perspective, we can see incidents where children become victims of criminal acts from a criminological perspective. Criminology sees the incident as an event that is avoided from relevant aspects, such as sociology, psychology, and biology. The existence of criminology is related to disciplines that refer to the conception of criminal cases related to crime, where it is closely related to the existence of law and violations of social norms seen from various aspects. Violence in children must be viewed holistically, not only from a legal perspective but also from a criminological perspective to see violence perpetrated against children from the root of the problem.